Effects of age, sex, and persistent organic pollutants on DNA methylation in children. (26th December 2013) - Huen, Karen; Yousefi, Paul; Bradman, Asa; Yan, Liying; Harley, Kim G.; Kogut, Katherine; Eskenazi, Brenda; Holland, Nina; O'Hagan, Heather; Tang, Winnie
<x xml:space="preserve">Abstract</x> Epigenetic changes such as DNA methylation may be a molecular mechanism through which environmental exposures affect health. Methylation of Alu and long interspersed nucleotide elements (LINE‐1) is a well‐established measure of DNA methylation often used in epidemiologic studies. Yet, few studies have examined the effects of host factors on LINE‐1 and Alu methylation in children. We characterized the relationship of age, sex, and prenatal exposure to persistent organic pollutants (POPs), dichlorodiphenyl trichloroethane (DDT), dichlorodiphenyldichloroethylene (DDE), and polybrominated diphenyl ethers (PBDEs), with DNA methylation in a birth cohort of Mexican‐American children participating in the CHAMACOS study. We measured Alu and LINE‐1 methylation by pyrosequencing bisulfite‐treated DNA isolated from whole blood samples collected from newborns and nine‐year old children (n = 358). POPs were measured in maternal serum during late pregnancy. Levels of DNA methylation were lower in nine‐year olds compared to newborns and were higher in boys compared to girls. Higher prenatal DDT/E exposure was associated with lower Alu methylation at birth, particularly after adjusting for cell type composition (P = 0.02 for o, p' ‐DDT). Associations of POPs with LINE‐1 methylation were only identified after examining the co‐exposure of DDT/E with PBDEs simultaneously. Our data suggest that repeat element methylation can be an informative marker of epigenetic differences by age and sex and that prenatal exposure to POPs may be linked to hypomethylation in fetal blood. Accounting for co‐exposure to different types of chemicals and adjusting for blood cell types may increase sensitivity of epigenetic analyses for epidemiological studies. Environ. Mol. Mutagen. 55:209–222, 2014. © 2013 Wiley Periodicals, Inc.